2021
DOI: 10.1007/s11430-020-9747-1
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen cycle and a habitable Earth

Abstract: As an important contributor to the habitability of our planet, the oxygen cycle is interconnected with the emergence and evolution of complex life and is also the basis to establish Earth system science. Investigating the global oxygen cycle provides valuable information on the evolution of the Earth system, the habitability of our planet in the geologic past, and the future of human life. Numerous investigations have expanded our knowledge of the oxygen cycle in the fields of geology, geochemistry, geobiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 197 publications
(239 reference statements)
0
9
0
Order By: Relevance
“…TOP, for example, is a biological process that absorbs energy from sunlight to synthesize oxygen and carbohydrate molecules from carbon dioxide and water. This process seems simple, but it is closely associated with other essential processes in the thermal cycle (e.g., temperature variations), hydrological cycle (e.g., water storage), and biogeochemical cycle (e.g., carbon fixation) (Huang et al., 2021). Therefore, many studies suggested an origin of TOP was close in time to “Great Oxidation Event” and the rise of atmospheric oxygen was directly driven by the evolution of terrestrial ecosystem (Huang et al., 2021; Soo et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TOP, for example, is a biological process that absorbs energy from sunlight to synthesize oxygen and carbohydrate molecules from carbon dioxide and water. This process seems simple, but it is closely associated with other essential processes in the thermal cycle (e.g., temperature variations), hydrological cycle (e.g., water storage), and biogeochemical cycle (e.g., carbon fixation) (Huang et al., 2021). Therefore, many studies suggested an origin of TOP was close in time to “Great Oxidation Event” and the rise of atmospheric oxygen was directly driven by the evolution of terrestrial ecosystem (Huang et al., 2021; Soo et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This process seems simple, but it is closely associated with other essential processes in the thermal cycle (e.g., temperature variations), hydrological cycle (e.g., water storage), and biogeochemical cycle (e.g., carbon fixation) (Huang et al., 2021). Therefore, many studies suggested an origin of TOP was close in time to “Great Oxidation Event” and the rise of atmospheric oxygen was directly driven by the evolution of terrestrial ecosystem (Huang et al., 2021; Soo et al., 2017). Based on this, we also analyzed variables related to climatic‐TOP interconnects, plant‐TOP interconnects, soil‐TOP interconnects, and microbial‐TOP interconnects, as well as climatic‐ plant‐ soil‐ and microbial indicator interconnects.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the surface temperature advection may affect cloud albedo in other ways than by affecting the moisture in cloud layers. Furthermore, dust can affect the meteorological environment through radiative effects; consequently, the positive coefficient found in this study may be a reflection of their effects (Sun and Zhao, 2020;Huang et al, 2021). The coefficients of the omega700 were negative for both datasets.…”
Section: The Impacts Of Different Aerosol Types and Meteorological Factors On Cloud Albedo Changesmentioning
confidence: 64%
“…McCoy et al (2018) have also validated the influence of SS on N d with up-to-date observations. As submicron SS in the MERRA-2 reanalysis data can be simply predicted from wind speed and SST by a parameterization (Jaeglé et al, 2011;McCoy et al, 2018;Li et al, 2018), the effect of SS on the cloud albedo may be dependent on the relationship be-tween the cloud albedo and near-surface wind speed, which may explain the limited effect of SS on the cloud albedo.…”
Section: The Impacts Of Different Aerosol Types and Meteorological Factors On Cloud Albedo Changesmentioning
confidence: 99%
“…As a necessity for the survival of almost all living organisms on Earth, atmospheric oxygen (O 2 ) is one of the most critical gases in the atmosphere. However, continuous O 2 observations at ppm resolution are quite sparse since detecting minor O 2 variations against a large natural background is quite challenging . Only a few organizations have conducted long-term atmospheric O 2 measurements, mostly in the natural background.…”
Section: Introductionmentioning
confidence: 99%